2007
DOI: 10.1111/j.1365-2699.2007.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA ploidy‐level variation in native and invasive populations of Lythrum salicaria at a large geographical scale

Abstract: Aim  This study aimed to document precisely the patterns of DNA ploidy variation in the native and secondary ranges of Lythrum salicaria distribution. The hypothesis that species invasiveness had been induced by a switch in ploidy level was addressed. Location  Europe, Middle East, North America. Methods  DNA ploidy levels of 1884 progenies of 578+ plants collected at 124 localities were determined by DAPI flow cytometry. Results  Large cytotype variation (2x, 3x, 4x and 6x) was found across the native area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
3
37
1
Order By: Relevance
“…This is in accordance with surveys that had been conducted by Fernald (1903) and Mulligan (1958) in eastern North America where only a few populations of L. ircutianum were found. The higher invasion success of the diploid L. vulgare is in contrast to studies that found a positive association between polyploidy and invasiveness in plants (Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009;Pandit et al 2011Pandit et al , 2014te Beest et al 2012). The higher abundance of L. vulgare in the introduced range could potentially be explained by differences in introduction pressure between the two species.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This is in accordance with surveys that had been conducted by Fernald (1903) and Mulligan (1958) in eastern North America where only a few populations of L. ircutianum were found. The higher invasion success of the diploid L. vulgare is in contrast to studies that found a positive association between polyploidy and invasiveness in plants (Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009;Pandit et al 2011Pandit et al , 2014te Beest et al 2012). The higher abundance of L. vulgare in the introduced range could potentially be explained by differences in introduction pressure between the two species.…”
Section: Discussioncontrasting
confidence: 63%
“…Polyploidy has been found to be overrepresented in invasive plants (Pandit et al 2011(Pandit et al , 2014 and in various taxa with more than one ploidy level in the native range, only polyploids have become invasive (e.g. Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009). Furthermore, polyploids are expected to exhibit increased concentrations of secondary metabolites compared to their diploid progenitors and may therefore experience greater levels of herbivore resistance (Levin 1983;Dhawan and Lavania 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This is an open question, but the many cases where both cytotypes occur in their native range but only polyploids do in the invasive ranges (Lafuma et al, 2003;Mandák et al, 2005;Kubátová et al, 2007;Schlaepfer et al, 2008;Treier et al, 2009) suggest a potential pre-adaptation of polyploids for invasiveness (te Beest et al, 2012). However, environmental stresses also increase the rate of unreduced gamete formation and thus of polyploidization events (Bretagnolle and Thompson, 1995;Ramsey and Schemske, 1998).…”
Section: The Long-term Gains Enhanced Invasiveness and Colonization Pmentioning
confidence: 99%
“…We suggest, therefore, that knowledge of polyploidy of the germplasm of C. ciliaris introduced in these areas is essential in comparative studies of invasive and native populations. Critical analysis of the relationship between invasiveness and polyploidy will require study of the polyploid complex, in which one may directly compare polyploids and their diploid relatives under field conditions (Kubátová et al 2008;Treier et al 2009;Schlaepfer et al 2010).…”
Section: Conclusion: Insights For Conservation and Invasion Biologymentioning
confidence: 99%